2018
DOI: 10.1371/journal.pone.0202797
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of atherosclerosis in apolipoprotein E-deficient mice by combined RNA interference of lipoprotein-associated phospholipase A2 and YKL-40

Abstract: To test the hypothesis that combined RNA interference (RNAi) of lipoprotein-associated phospholipase A2 (Lp-PLA2) and YKL-40 is superior to RNAi of Lp-PLA2 or YKL-40 alone in ameliorating atherosclerosis. A total of 120 apolipoprotein E-deficient mice (apoE-/- mice) were randomly divided into five groups, including the vehicle alone, scrambled RNAi, Lp-PLA2 RNAi, YKL-40 RNAi, and combined Lp-PLA2 and YKL-40 RNAi groups. Constrictive collars were used to induce plaque formation. Lp-PLA2 RNAi and YKL-40 RNAi vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…After anesthesia (40 mg/kg pentobarbital sodium i.p.) a constrictive silastic tube (0.30 mm) was applied to elicit plaque formation 1,11,12 . The mice were divided into three groups (n = 24 in each group): the control group, the valsartan group and the LCZ696 group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After anesthesia (40 mg/kg pentobarbital sodium i.p.) a constrictive silastic tube (0.30 mm) was applied to elicit plaque formation 1,11,12 . The mice were divided into three groups (n = 24 in each group): the control group, the valsartan group and the LCZ696 group.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA from the cells or the carotid arteries was extracted using Trizol reagent in accordance with the supplier’s instructions (CoWin Bioscience). qPCR analysis was conducted as described previously 1,11,12 . The relative expressions of IL-6, MCP-1 and MMP-8 mRNAs were quantified using SYBR green with the ABI Prism 7500 sequence detection system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…152 In addition, downregulating the expression of the PLA2G7 gene by RNA interference could induce ameliorative inflammation and atherosclerosis in apolipoprotein E-deficient mice. 153 Taken together, these findings indicate that Lp-PLA2 might be crucial during the development of atherosclerosis and in determining plaque instability via inflammatory pathways.…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 82%
“…Furthermore, many large‐scale epidemiological studies have found that elevated plasma Lp‐PLA2 levels are associated with an increased risk of coronary disease, stroke, and/or mortality, further substantiating the proatherogenic role of Lp‐PLA2 . In addition, downregulating the expression of the PLA2G7 gene by RNA interference could induce ameliorative inflammation and atherosclerosis in apolipoprotein E‐deficient mice . Taken together, these findings indicate that Lp‐PLA2 might be crucial during the development of atherosclerosis and in determining plaque instability via inflammatory pathways.…”
Section: Biological Functions and Disease Implicationsmentioning
confidence: 84%